The Budding Economy of a Flower-The Case of 'Mangaluru Mallige' - Subramanian, Melarkode P.; Mulleria, Venugopal (Indian Journal of Marketing, 2006)
'Mallige' in Kannada language means jasmine. 'Mangaluru' is the vernacular pronunciation for Mangalore, a taluk in Dakshina Kannada (DK) District of coastal Karnataka. 'Mangalore Mallige' is a variety of jasmine and it is so called because its commercial potential was first exploited by the village households in and around Mangalore. 'Mangalore Mallige' (MM) occupies an unique position in the life and economy of Udupi and Dakshina Kannada Districts in Coastal Karnataka so much so it is not only a household word but also a source of income and occupation for quite a number of households in this part of the country.